Human Liver Stem Cells Suppress T-Cell Proliferation, NK Activity, and Dendritic Cell Differentiation. (4th April 2016) - Bruno, Stefania; Grange, Cristina; Tapparo, Marta; Pasquino, Chiara; Romagnoli, Renato; Dametto, Ennia; Amoroso, Antonio; Tetta, Ciro; Camussi, Giovanni
Abstract : Human liver stem cells (HLSCs) are a mesenchymal stromal cell-like population resident in the adult liver. Preclinical studies indicate that HLSCs could be a good candidate for cell therapy. The aim of the present study was to evaluate the immunogenicity and the immunomodulatory properties of HLSCs on T-lymphocytes, natural killer cells (NKs), and dendritic cells (DCs) in allogeneic experimental settings. We found that HLSCs inhibited T-cell proliferation by a mechanism independent of cell contact and dependent on the release of prostaglandin E2 (PGE2 ) and on indoleamine 2, 3-dioxygenase activity. When compared with mesenchymal stromal cells (MSCs), HLSCs were more efficient in inhibiting T-cell proliferation. At variance with MSCs, HLSCs did not elicit NK degranulation. Moreover, HLSCs inhibited NK degranulation against K562, a NK-sensitive target, by a mechanism dependent on HLA-G release. When tested on DC generation from monocytes, HLSCs were found to impair DC differentiation and DCs ability to induce T-cell proliferation through PGE2 . This study shows that HLSCs have immunomodulatory properties similar to MSCs, but, at variance with MSCs, they do not elicit a NK response.